the Implementasi Metode Simple Additive Weighting dalam Penentuan Penerima Manfaat Program pada Desa Lokus Stunting - Fandli Supandi; Abdul Gani Fadhlulrahman S H Lihawa (Informatik : Jurnal Ilmu Komputer, 2026)
Stunting a serious nutritional problem often exacerbated by poor environmental sanitation, makes the Community-Based Sanitation (Sanimas) program vital for expanding sanitation access. Given that the manual selection process for Sanimas beneficiaries is time-consuming and inefficient , this study aims to develop a Decision Support System (DSS) to determine recipient priorities objectively and measurably. The research implements the Simple Additive Weighting (SAW) method, an effective Multi-Criteria Decision Analysis (MCDA) technique for multi-criteria decision problems. The SAW method operates by normalizing the decision matrix and calculating the weighted sum of performance ratings to obtain the final preference value . The criteria used are Low-Income Community (C1), Stunting Risk Family (C2), Sanitation Access (C3), Availability of Water Source (C4), Own House (C5), Priority Condition (C6), and Number of Family Members in the Household (C7) 7, with a total weight of 100. The implementation results on sample data in Molintogupo Village, Bone Bolango, show that alternative “SD” obtained the highest Preference Value of 97 (Rank 1). In conclusion, the SAW method is proven effective in systematically generating a ranking of beneficiaries 10; however, the presence of identical preference values among several candidates indicates that the final decision still requires contextual consideration and policy from village-level stakeholders.